RhoE Binds to ROCK I and Inhibits Downstream Signaling - Riento, Kirsi (American Society for Microbiology, 2003)
RhoE belongs to the Rho GTPase family, the members of which control actin cytoskeletal dynamics. RhoE induces stress fiber disassembly in a variety of cell types, whereas RhoA stimulates stress fiber assembly. The similarity of RhoE and RhoA sequences suggested that RhoE might compete with RhoA for interaction with its targets. Here, we show that RhoE binds ROCK I but none of the other RhoA targets tested. The interaction of RhoE with ROCK I was confirmed by coimmunoprecipitation of the endogenous proteins, and the two proteins colocalized on the trans-Golgi network in COS-7 cells. Although RhoE and RhoA were not able to bind ROCK I simultaneously, RhoE bound to the amino-terminal region of ROCK I encompassing the kinase domain, at a site distant from the carboxy-terminal RhoA-binding site. Overexpression of RhoE inhibited ROCK I-induced stress fiber formation and phosphorylation of the ROCK I target myosin light chain phosphatase. These data suggest that RhoE induces stress fiber disassembly by directly binding ROCK I and inhibiting it from phosphorylating downstream targets.